Enhanced hydrogen storage performance of Cu3(BTC)2 in situ inserted with few-layer silicon-based nanosheets. (22nd July 2022) - Liu, Fei; Zhao, Yanliang; Hou, Hua; Zhao, Yuhong; Wang, Zhongmin; Huang, Zhimin
Abstract: Silicon-based nanosheets (SNS) were synthesised via a mild (60 °C) and time-saving (8 h) modified topochemical method. Then, Cu3 (BTC)2 and SNS@Cu3 (BTC)2 were successfully synthesised by microwave irradiation, and their characteristics and hydrogen storage performance were analysed by multiple techniques. The accordion-like SNS exhibited void spaces, a unique low buckled structure, and ultrathin, almost transparent, loosely stacked layers with a high specific surface area (362 m 2 /g). After in-situ synthesis with Cu3 (BTC)2, the SNS compound achieved a high specific surface area (1526 m 2 /g), outstanding hydrogen storage performance (5.6 wt%), and a desirable hydrogen diffusion coefficient (10 −7 ). Thus, SNS doping improved the hydrogen storage performance of Cu3 (BTC)2 by 64% through electron transfer reactions with Cu enabled by the unique composite nanostructure of SNS@Cu3 (BTC)2 . This study presents a promising method of synthesising SNS and porous composite materials for hydrogen storage. Graphical abstract: Image 1 Highlights: We present an improved topochemical synthesis method for silicon nanosheets (SNS). We synthesise SNS-doped Cu3 (BTC)2 via microwave irradiation for hydrogen storage. SNS exhibit a unique low-buckled structure and high specific surface area (362 m 2 /g). More active metal sites and small pores improve the hydrogen storage capacity. This promising method can generate porous composite materials for hydrogen storage.